سلوک العتبات المصنعة من الخرسانة المحورة بالبولیمروالخالیة من الرکام الناعم - nan, nan; Battal Najim, Khalid; nan, nan (Iraqi Journal of Civil Engineering, 2007)
This research includes a study of the behavior of beams made from No-fine concrete using 10 maximum size of aggregate and improved by SBR polymer. From test results, the effect of addition of polymer to concrete leads to improved compressive and flexural strengths, The beams improved by polymer failed under loads more than the beams which were made from reference concrete. The percentage increases in compressive strength for No-fines polymer concrete compared with reference concrete were (41%, 58, 38%) for ages (3,7,28) days respectively